2010
DOI: 10.1007/s12011-010-8712-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Vitamin C and E Combination on Element and Oxidative Stress Levels in the Blood of Operative Patients Under Desflurane Anesthesia

Abstract: We investigated effects of vitamin C and E (VCE) administration on desflurane-induced oxidative toxicity and element changes in the blood of operative patients under desflurane general anesthesia. Forty American Society of Anesthesiologists I or II Physical Status adult patients were scheduled for elective surgery. The patients were randomly divided into two groups. Control and VCE group was introduced to anesthesia with desflurane. VCE was administreted to patients in the control and VCE group before 1 hour o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…At 72 h following the administration of desflurane general anesthesia, plasma lipid peroxidation levels were higher and vitamin C remained unaltered in operative patients who did not receive vitamin C and vitamin E before surgery than in those who received these vitamins [36]. In our patients, MDA and free 8-isoprostane concentrations did not change along chemotherapy, and zinc supplementation did not affect the plasma concentrations of these lipid peroxidation markers.…”
Section: Discussionmentioning
confidence: 44%
“…At 72 h following the administration of desflurane general anesthesia, plasma lipid peroxidation levels were higher and vitamin C remained unaltered in operative patients who did not receive vitamin C and vitamin E before surgery than in those who received these vitamins [36]. In our patients, MDA and free 8-isoprostane concentrations did not change along chemotherapy, and zinc supplementation did not affect the plasma concentrations of these lipid peroxidation markers.…”
Section: Discussionmentioning
confidence: 44%
“…Administration of vitamin E has been reported to have an important protective effect against chemotherapy‐induced peripheral nerve damage 29 . In addition, vitamins E and C in combination, have been reported to reduce the oxidative damage induced by certain anesthetic drugs 30 and exercise 31 . In the present study, we found that VCE supplementation markedly increased ( P < 0·01) the levels of all free radical scavenging enzymes, SOD, CAT, GST and GR (Table 2) as well as of the non‐enzymatic antioxidant, GSH (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…3 MDA results from the breakdown of lipid peroxyl radicals and oxidizes protein molecules, and thus, it is both an indicator and effector of oxidative stress. 3 MDA results from the breakdown of lipid peroxyl radicals and oxidizes protein molecules, and thus, it is both an indicator and effector of oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…The concentrations of these metabolites are kept under a precise control. 3 ROS are scavenged by antioxidant defence systems including enzymes and non-enzyme species such as vitamin C, vitamin E, vitamin A, b-carotene, glutathione peroxidase (GSH-Px) and reduced glutathione (GSH). 2 Also, recent studies have shown that ROS mediated oxidative stress can cause cellular damage.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation